Skin melanoma: present possibilities of treatment in Poland based on own experiences of melanoma patients’ course and current review of literature - Kycler, Witold; Teresiak, Marek (Contemporary Oncology/Współczesna Onkologia, 2006)
Melanoma is one of the most malignant human cancers with a still increasing factor of incidence. Skin melanoma diagnostics is based on clinical estimation of skin changes, precisely establishing clinical advanced needs to employ histopathological methods and some imaging techniques Early diagnostics and prevention are the most important elements in prophylaxis and successful treatment of melanoma patients. In this aspect it seems to be most important to separate the group of high risk. The method of choice in most melanoma cases is surgical resection. In this article we present the results of treatment of melanoma patients operated on in the Wielkopolska Cancer Centre. In a special manner we focused our attention on lymph node surgery. Similarly to results obtained by other authors we observed a strong correlation between presence of lymph node metastasis and patients’ survival. Adjuvant therapies were discussed in advanced melanomas. Here we present the current knowledge on prevention, diagnostics and melanoma treatment based on a review of the medical literature and own experience with management of melanoma cases.